Wastage in primary education: dropout and repetition at primary schools in Palpa District - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2014)
The study aimed at analyzing wastage in primary education focusing on dropout and grade repetition in primary level and is limited to the case of Palpa district. The study is based on School Mapping Database of District Education Office, Palpa, 2009. Primary education in Palpa district is characterized by high rate of dropout (9.7 percent) and grade repetition (14.6 percent). This indicates the low efficiency and high educational wastage. The scenario of dropout and repetition is not uniform across the district and varies sharply by resource centers. The high wastage in primary education in Palpa district clearly indicates the great challenge in achieving the goal of universal primary education the ‘quality basic education for all’. Failure in examination, poverty and ignorance of the parents are the main reasons for a high repetition. In many instances, especially, poor and dalit children left the schools after the distribution of scholarships and get enrolled again next year hopping the same. Likewise, failure in examination, poverty and ignorance of parents and cultural factors are responsible for high dropout. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11511 The Third Pole: Journal of Geography Vol.8-10, pp. 43-50: 2010